2017
DOI: 10.1186/s13058-016-0791-4
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between crown-like structures and sex-steroid hormones in breast adipose tissue and serum among postmenopausal breast cancer patients

Abstract: BackgroundPostmenopausal obesity is associated with increased circulating levels of androgens and estrogens and elevated breast cancer risk. Crown-like structures (CLS; microscopic foci of dying adipocytes surrounded by macrophages) are proposed to represent sites of increased aromatization of androgens to estrogens. Accordingly, we examined relationships between CLS and sex-steroid hormones in breast adipose tissue and serum from postmenopausal breast cancer patients.MethodsFormalin-fixed paraffin embedded be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
75
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(83 citation statements)
references
References 24 publications
5
75
1
2
Order By: Relevance
“…N=20 studies have been identified that were conducted in patients with different cancer types (breast, colorectal, esophageal, endometrial, prostate, and ENT) to investigate the crosstalk between patients’ adipose tissue and carcinomas (see Table 1) (8,6475). …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…N=20 studies have been identified that were conducted in patients with different cancer types (breast, colorectal, esophageal, endometrial, prostate, and ENT) to investigate the crosstalk between patients’ adipose tissue and carcinomas (see Table 1) (8,6475). …”
Section: Resultsmentioning
confidence: 99%
“…The majority of human studies have been conducted in breast cancer patients (n=7) (66,68,70,7578). Other studies have been implemented in cancers of the gastrointestinal tract (colorectal cancer (n=4) (8,64,71,73), esophageal cancer (n=2) (65,79), combined (colorectal and esophageal) (n=1) (80)), reproductive cancer (endometrial (n=1) (72), prostate (n=4) (69,74,81,82)), or ENT tract (tongue (n=1) (83)).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…17). Importantly, an increase in the estrone:androstenedione ratio was found in breast tissue from postmenopausal breast cancer patients that contained CLS (18). Interestingly, inflamed adipose tissue has recently been shown to release cell-free DNA capable of stimulating insulin resistance (19).…”
Section: Articles By Iyengar Et Al Published In This Issue Cancer Prmentioning
confidence: 99%